Accessibility of masjid design in Malaysia - Ahmad Sarkawi, Azila; Tukiman, Izawati; Abd Samad, Nur Amirah; Abdul Rahim, Asiah (IIUM Press, International Islamic University Malaysia, 2016)
In Islam, masjid plays pivotal role as a center of gravity. Its functions range from not only a place for performing prayer, but up to social congregation and welfare facilities like sport, rehabilitation center, information center etc. Furthermore, masjid is for all walks of life. It is a collective obligation to ensure masjid is accessible to all, able and disabled person. The formulation of MS 1184 and MS 2577 is a concerted effort towards universal design of masjid. The former becomes a source of reference to access audit while the latter facilitates the development of masjid in Malaysia. The paper presents a result of access audit to three selected masjid in Malaysia namely Masjid Sultan Idris Shah, Ipoh, Masjid Negeri, Seremban and Masjid Tunku Mizan, Putrajaya. Using a case study method, a set of criteria for access audit was used against the selected masjid to identify the state of their accessibility and connectivity. The study found that Masjid Sultan Idris Shah, Ipoh, Masjid Negeri, Seremban and Masjid Tunku Mizan, Putrajaya achieve MS1184:2014. MS1184:2014 were proposed to enhance the accessibility to the building.